Upaya Meningkatkan Hasil Belajar Peserta Didik dengan Menggunakan Media Audio Visual pada Pelajaran Bahasa Indonesia Kelas V SDN-5 Menteng Palangka Raya - Hendri Gunawan; A'am Rifaldi Khunaifi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine whether or not there is an increase in activity and learning outcomes of students in Indonesian language lessons, the subject of listening to population density using audio grade V media in Menteng-5 Elementary School Palangkaraya. The research method used in this study is the Classroom Action Research (CAR) method. With the number of research subjects 28 students. There was an increase in the activity of students when the learning process of Indonesian Language especially listening to news using Audio Visual media in class V students of SDN-5 Menteng Palangkaraya this was evidenced by the results of the average activity of students namely 3.65 while the average activity teacher is 3.64. There has been an increase in learning outcomes after being distributed using audiovisual media listening to the news on Indonesian language lessons for students in the fifth-grade of Menteng-5 SDN Palangkaraya. This can be seen from the learning outcomes of students, in the first cycle that is 73.03 and the classical completeness is 60.71% and in the second cycle it increases to 81.25 and the classical completeness is 100%.